2015
DOI: 10.1007/s10549-014-3252-8
|View full text |Cite
|
Sign up to set email alerts
|

History of oral contraceptive use in breast cancer patients: impact on prognosis and endocrine treatment response

Abstract: The purpose was to study oral contraceptive (OC) use in relation to breast cancer events and endocrine treatment response in a prospective population-based cohort, because it is unclear whether history of OC use impacts on prognosis in breast cancer patients. Between 2002 and 2011, 994 primary breast cancer patients without preoperative treatment were enrolled in Lund, Sweden and followed until December 2012. History of OC use was obtained from preoperative questionnaires. Tumor characteristics, clinical data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
2
11
1
1
Order By: Relevance
“…OC use prior to age 20 years was significantly associated with lower COX‐2 expression in the present study and low COX‐2 expression was associated with worse short‐term prognosis. In line with this, OC use prior to age 20 years was previously reported to be associated with a worse prognosis among patients younger than 50 years in this cohort . Early OC use may carry long‐term impact on the tumor environment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…OC use prior to age 20 years was significantly associated with lower COX‐2 expression in the present study and low COX‐2 expression was associated with worse short‐term prognosis. In line with this, OC use prior to age 20 years was previously reported to be associated with a worse prognosis among patients younger than 50 years in this cohort . Early OC use may carry long‐term impact on the tumor environment.…”
Section: Discussionsupporting
confidence: 86%
“…However, any history of OC use prior to diagnosis, and not early OC use modified the association between COX‐2 expression and prognosis. Ever OC use was also associated with improved prognosis among AI‐treated patients 50 years or older in the previous study . However, there was no association between COX‐2 expression and prognosis in AI‐treated patients in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…A prior study using the same cohort has shown that smoking is associated with a higher risk of recurrence and death among AI-treated patients (31). A different study performed within the BCBlood study showed that ever a history of oral contraceptives use led to a lower risk of recurrence among AI-treated patients than non-users of oral contraceptives (43). The interaction between MHT and AI treatment was still significant when adjusted for smoking and ever oral contraceptive use.…”
Section: Discussionmentioning
confidence: 87%
“…Women who had begun use before the age of 20 and were older than age 50 at the time of diagnosis showed no increased risk compared to age similar cases who began use later (HR = 0.70; 95% CI = 0.33–1.46). Women in this study took contraceptives for an average of 6 years, although the duration of use varied from 2 ½ to 12 years [ 169 ].…”
Section: Evidence Linking Environmental Factors and Breast Cancermentioning
confidence: 99%